Intra-generational inequalities in young people's political participation in Europe: The impact of social class on youth political engagement. (February 2022) - Grasso, Maria; Giugni, Marco
The declining political engagement of youth is a concern in many European democracies. However, young people are also spearheading protest movements cross-nationally. While there has been research on political inequalities between generations or inter-generational differences, research looking at differences within youth itself, or inequalities between young people from different social backgrounds, particularly from a cross-national perspective, is rare. In this article, we aim to fill this gap in the literature. Using survey data from 2018 on young people aged 18–34 years, we analyse how social class background differentiates groups of young people in their political engagement and activism across nine European countries. We look at social differentiation by social class background for both political participation in a wide variety of political activities including conventional, unconventional, community and online forms of political participation, and at attitudes linked to broader political engagement, to paint a detailed picture of extant inequalities amongst young people from a cross-national perspective. The results clearly show that major class inequalities exist in political participation and broader political engagement among young people across Europe today.